2014
DOI: 10.1007/s10815-014-0247-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of red light on the development and quality of mammalian embryos

Abstract: Purpose To assess irradiance and total energy dose from different microscopes during the in-vitro embryonic developmental cycle in mouse and pig and to evaluate its effect on embryonic development and quality in pig. Method Spectral scalar irradiance (380-1050 nm) was measured by a fiber-optic microsensor in the focal plane of a dissection microscope, an inverted microscope and a timelapse incubation system. Furthermore, the effect of three different red light levels was tested in the time-lapse system on mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 26 publications
0
18
1
Order By: Relevance
“…Mio et al reported no difference in clinical pregnancy rate after time-lapse observation, compared with standard incubation [26]. Li et al proved that in both mouse zygotes and porcine embryos, red light used in the time-lapse incubator does not decrease blastocyst formation compared to standard incubation [56]. In addition, a study published by Nakahara et al concluded that there is a little effect on embryos from exposure during time-lapse observation, therefore can be securely used for clinical purposes [27].…”
Section: Discussionmentioning
confidence: 99%
“…Mio et al reported no difference in clinical pregnancy rate after time-lapse observation, compared with standard incubation [26]. Li et al proved that in both mouse zygotes and porcine embryos, red light used in the time-lapse incubator does not decrease blastocyst formation compared to standard incubation [56]. In addition, a study published by Nakahara et al concluded that there is a little effect on embryos from exposure during time-lapse observation, therefore can be securely used for clinical purposes [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, green and red light seems to have no or negligible effects on cellular growth suppression compared with blue light. Both green and red light emits longer wavelengths compared with blue light (Korhonen et al, ; Kuse et al, ; Li et al, , b; Rohringer et al, ). Since longer‐wavelength light contains less energy, it is less likely to be absorbed by biological molecules and thus not mediate a reaction at the threshold level to cause damage associated with shorter wavelengths.…”
Section: Discussionmentioning
confidence: 99%
“…Although the impact of light on tissue is diverse (Fodor et al, ; Tuchin, ), visible light wavelengths seem to be closely associated with the incidence and extent of cellular damage, that is, the damage is more prominent in shorter wavelengths than in those that are longer (Takenaka et al, ; Oh et al, ; Kuse et al, ; Contin et al, ; Mignon et al, ; Rohringer et al, ). The harmful effects associated with shorter wavelengths include potential damage/alteration to the gene, deoxyribonucleic acid (DNA), or protein, which leads to lower cell viability, deterioration in cell quality, and acceleration of damage or death (Takenaka et al, ; Li et al, ; Contin et al, ). These unwanted consequences of light are also related to the etiology of many diseases, such as cellular aging, age‐related pathologies, and tumorigenesis (Setlow et al, ; Setlow and Woodhead, ).…”
Section: Introductionmentioning
confidence: 99%
“…[259][260][261][262][263][264][265] This appears to be dependent on the wavelength of light, and longer wavelengths have less effect on stress response and development of animal embryos. 262,266,267 Although there is no evidence regarding the effect of light on human embryos, the use of filters on microscopes has been suggested to reduce the potentially damaging effect of light in IVF clinics. 268 The light used during time-lapse photography is usually red and therefore less likely to cause a stress response, and exposure is also very brief.…”
Section: Lightmentioning
confidence: 99%